2023
DOI: 10.1038/s41467-023-37868-0
|View full text |Cite
|
Sign up to set email alerts
|

Native doublet microtubules from Tetrahymena thermophila reveal the importance of outer junction proteins

Abstract: Cilia are ubiquitous eukaryotic organelles responsible for cellular motility and sensory functions. The ciliary axoneme is a microtubule-based cytoskeleton consisting of two central singlets and nine outer doublet microtubules. Cryo-electron microscopy-based studies have revealed a complex network inside the lumen of both tubules composed of microtubule-inner proteins (MIPs). However, the functions of most MIPs remain unknown. Here, we present single-particle cryo-EM-based analyses of the Tetrahymena thermophi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 76 publications
4
70
0
Order By: Relevance
“…ENKUR is a MIP and is known to be positioned within the B tubule of the MT doublet 44 , and accordingly, our XL/MS data linked ENKUR directly to another B-tubule MIP, CFAP45, but not to other nearby MIPs, such as CFAP52 or PACRG (Figure 7A). Consistent with our interactome data, knockdown of ENKUR elicited a robust loss of CFAP45 localization in motile axonemes in Xenopus MCCs, providing the first known defect in ENKUR deficient axonemes.…”
Section: Xl/ms-directed Analysis Of Links Between Mips and Axonemal D...mentioning
confidence: 71%
See 1 more Smart Citation
“…ENKUR is a MIP and is known to be positioned within the B tubule of the MT doublet 44 , and accordingly, our XL/MS data linked ENKUR directly to another B-tubule MIP, CFAP45, but not to other nearby MIPs, such as CFAP52 or PACRG (Figure 7A). Consistent with our interactome data, knockdown of ENKUR elicited a robust loss of CFAP45 localization in motile axonemes in Xenopus MCCs, providing the first known defect in ENKUR deficient axonemes.…”
Section: Xl/ms-directed Analysis Of Links Between Mips and Axonemal D...mentioning
confidence: 71%
“…We therefore explored deeper into the ENKUR/CFAP45 protein interaction neighborhood. Our XL/MS demonstrate that the association involves the N-terminus of CFAP45 and C-terminus of ENKUR, regions otherwise unresolved in the recently published structure of the native Tetrahymena doublet microtubule (DMT) 89 . Moreover, the structure raises the possibility that like other MIPs 86 , ENKUR and/or CFAP45 may penetrate the MT doublet wall.…”
Section: Xl/ms-directed Analysis Of Links Between Mips and Axonemal D...mentioning
confidence: 79%
“…We first examined a 48-nm repeat cryo-EM density map from native DMTs of Tetrahymena WT ( CU428 strain) (Fig. 1A) (S. Kubo et al, 2023). We identified and modeled all visible αK40 loops of α-tubulins in the map, which are known to be almost 100% acetylated (Akella et al, 2010; Gaertig et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…We identified and modeled all visible αK40 loops of α-tubulins in the map, which are known to be almost 100% acetylated (Akella et al, 2010; Gaertig et al, 1995). Most Tetrahymena MIPs have been localized and identified in this map (S. Kubo et al, 2023). In contrast to the acetylated singlet microtubule structure (Eshun-Wilson et al, 2019), we observed many fully structured αK40 full (missing no more than two residues from residues 37 to 48) and partial structure loops (missing 3-5 residues) in DMT (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation